2002
DOI: 10.1046/j.1365-2842.2002.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture characteristics of carbon fibre, ceramic and non‐palladium endodontic post systems at monotonously increasing loads

Abstract: A carbon fibre post system, three non-palladium and one palladium metal post systems, two ceramic post systems, and a metal post system with a ceramic core were studied in vitro. The control group consisted of root-filled test teeth without posts. The test teeth were identical artificial roots of an upper central incisor made from a posterior composite whose module of elasticity was similar to that of natural dentine. All posts were cemented in the roots using Panavia 21 TC. Subsequently, standardized full cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 13 publications
2
90
1
13
Order By: Relevance
“…1 In these cases, the use of posts is recommended to promote retention of the final restoration. [2][3] The preservation of tooth structure is an important factor in the successful restoration of endodontically treated teeth. Some authors 4,5 have suggested that a tooth should have a minimum amount (2 mm) of coronal structure above the cementoenamel junction (CEJ) to ensure a proper shape of strength for a tooth.…”
Section: Introductionmentioning
confidence: 99%
“…1 In these cases, the use of posts is recommended to promote retention of the final restoration. [2][3] The preservation of tooth structure is an important factor in the successful restoration of endodontically treated teeth. Some authors 4,5 have suggested that a tooth should have a minimum amount (2 mm) of coronal structure above the cementoenamel junction (CEJ) to ensure a proper shape of strength for a tooth.…”
Section: Introductionmentioning
confidence: 99%
“…The placement of posts in endodontically treated teeth reduced stress in this area [3][4][5] . When the post is inserted into the root canal, some of its force is directed along the post length.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…32 Furthermore, sealers penetrate into dentin tubuli, and their bond strength to dentin and the bond strengths of the composite cements to the sealers may [32][33] To study the effect of composite gap size, the influence of the other factors should be avoided, if possible. The bond strengths of composites to root dentin of the various areas might differ, 3,18 but this factor could not be excluded in the current study. The bond strengths of several FRC post systems are expected to be different, due to their shape and composition; this is why only one FRC post system was used for the current study.…”
Section: Discussionmentioning
confidence: 88%
“…In these situations, post space preparation for a precisely fitting post would mean reduction of the root dentin, which could weaken the remaining tooth substance. The fabrication of an individually cast post in the dental laboratory, which is time and costintensive, [17][18][19] might be needed.…”
Section: Introductionmentioning
confidence: 99%